The influences of seismic load on dynamic deformation properties of rock material under different confining pressures - Zhou, Yongqiang; Yuan, Wei; Song, Dingfeng; Hu, Jun; Chai, Shaobo; Lai, Jie (Frontiers in Earth Science, 2023)
Long-term geological storage of carbon dioxide in underground engineering is the most economically viable option for reducing emissions of this greenhouse gas to the atmosphere. Underground engineering projects are often subjected to earthquakes during their lives, thus it is essential to investigate the deformation characteristics of surrounding rock of those underground engineering works subjected to seismic load under different confining pressures. To date, however, there have been notably few studies on the characteristics of rock materials under seismic load and the influences of seismic load on dynamic deformation properties of rock material under different confining pressures remain unclear. Therefore, a numerical study of the dynamic mechanical properties of a rock material (T2y6 marble) under Kobe seismic load with four different maximum stresses and four different confining pressures was conducted. The results show cyclic behavior, strain rate effect and damage are found in the stress-strain curves of the rock under simulated Kobe seismic load. Confining pressure can significantly limit the increases in lateral strain and volumetric strain, thus dilation can occur in the rock when the maximum stress of seismic load is large, and the confining pressure is small. Seismic load with small maximum stress cannot cause severe damage to the rock, but the influence is larger than that of static load. The maximum stress can be treated as a main factor affecting the damage to rock under seismic loads, while the effect of confining pressure thereon is smaller than that of the maximum stress. Furthermore, the relationships between deformation characteristics of the rock under these seismic loads, such as maximum strain, residual strain, plastic internal variable, deformation modulus, and maximum stress are different from that between the deformation characteristics and confining pressure.